2021
DOI: 10.1111/inm.12817
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors of anxiety and depression among nurses fighting coronavirus disease 2019 in China

Abstract: Anxiety and depression are common mental illnesses among nurses fighting coronavirus disease 2019 (COVID‐19). However, the precise factors that affect anxiety and depression in this population require further evaluation. This study aimed to explore factors associated with anxiety and depression among nurses fighting COVID‐19 in China. We used convenience sampling to recruit 282 nurses fighting COVID‐19 in three hospitals. Participants were questioned about demographic characteristics, daily working time, daily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 45 publications
(51 reference statements)
2
31
0
6
Order By: Relevance
“…A total of 191 articles were screened for inclusion criteria between the two searches; 32 were selected for this review (Figure 1 ). The studies were conducted from countries worldwide, including China ( n = 11) (Cai et al, 2020 ; Hu et al, 2020 ; Huang et al, 2020 ; Leng et al, 2020 ; Li et al, 2020 ; Liang et al, 2020 ; Lin et al, 2020 ; Liu et al, 2020 ; Lyu et al, 2020 ; Ou et al, 2020 ; Pang et al, 2021 ), Italy ( n = 1) (Catania et al, 2020 ), Iran ( n = 2) (Afshari et al, 2021 ; Meybodi & Mohammadi, 2020 ), France ( n = 1) (Altmayer et al, 2020 ), Japan ( n = 1) (Awano et al, 2020 ), Saudi Arabia ( n = 1) (Balay‐odao et al, 2021 ), the United States, ( n = 3) (Barzilay et al, 2020 ; LoGuidice & Bartos, 2021 ; Resnick, 2020 ), Singapore ( n = 1) (Goh et al, 2020 ), India ( n = 2) (Jose et al, 2020 ; Nathiya et al, 2021 ), Turkey ( n = 3) (Kılınç & Çelik, 2020 ; Yıldırım et al, 2020 ; Yörük & Güler, 2020 ), the Philippines ( n = 1) (Labrague & de los Santos, 2020 ), Canada ( n = 1) (Lapum et al, 2020 ), Spain ( n = 2) (Lorente et al, 2020 ; Luceño‐Moreno et al, 2020 ), the United Kingdom ( n = 1) (Roberts et al, 2021 ) and Ethiopia ( n = 1) (Tsehay et al, 2020 ). A summary of the articles included in this integrative review and their results can be found in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 191 articles were screened for inclusion criteria between the two searches; 32 were selected for this review (Figure 1 ). The studies were conducted from countries worldwide, including China ( n = 11) (Cai et al, 2020 ; Hu et al, 2020 ; Huang et al, 2020 ; Leng et al, 2020 ; Li et al, 2020 ; Liang et al, 2020 ; Lin et al, 2020 ; Liu et al, 2020 ; Lyu et al, 2020 ; Ou et al, 2020 ; Pang et al, 2021 ), Italy ( n = 1) (Catania et al, 2020 ), Iran ( n = 2) (Afshari et al, 2021 ; Meybodi & Mohammadi, 2020 ), France ( n = 1) (Altmayer et al, 2020 ), Japan ( n = 1) (Awano et al, 2020 ), Saudi Arabia ( n = 1) (Balay‐odao et al, 2021 ), the United States, ( n = 3) (Barzilay et al, 2020 ; LoGuidice & Bartos, 2021 ; Resnick, 2020 ), Singapore ( n = 1) (Goh et al, 2020 ), India ( n = 2) (Jose et al, 2020 ; Nathiya et al, 2021 ), Turkey ( n = 3) (Kılınç & Çelik, 2020 ; Yıldırım et al, 2020 ; Yörük & Güler, 2020 ), the Philippines ( n = 1) (Labrague & de los Santos, 2020 ), Canada ( n = 1) (Lapum et al, 2020 ), Spain ( n = 2) (Lorente et al, 2020 ; Luceño‐Moreno et al, 2020 ), the United Kingdom ( n = 1) (Roberts et al, 2021 ) and Ethiopia ( n = 1) (Tsehay et al, 2020 ). A summary of the articles included in this integrative review and their results can be found in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Overall, resilience scores among frontline healthcare workers during the COVID‐19 pandemic in the studies reviewed were in the moderate range (CD‐RISC range = 35.54–92.77) (Afshari et al, 2021 ; Cai et al, 2020 ; Jose et al, 2020 ; Kilinc & Celik, 2020; Leng et al, 2020 ; Li et al, 2020 ; Lin et al, 2020 ; Lyu et al, 2020 ; Nathiya et al, 2021 ; Ou et al, 2020 ; Pang et al, 2021 ). In two studies conducted in Asia, physicians had higher resilience scores than nurses (Awano et al, 2020 ; Lin et al, 2020 ), and support staff had the highest resilience scores (mean = 73.48) compared with doctors (mean = 67.78) and nurses (mean = 64.86) (Lin et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 40,489 nurses in studies where the percentage of men and women was specified, 95.81% (n = 38,792) were women. In fifteen of the studies [6,[25][26][27][28][29][30][31][32][33][34][35][36][37][38], the average age of respondents was determined by the mean, which ranged from 28.8 to 45.1 years; in the remaining studies [9,23,[39][40][41][42][43], the age distribution was described by categories. In one study [24], neither average age nor age categories was given.…”
Section: Description Of Included Studiesmentioning
confidence: 99%
“…18 Anxiety and depression were again reported among nurses in China whereas the three most important variables that accounted for depression, anxiety, and stress were resilience, coping styles, and sleep quality. 20 Similarly, a study from Portuguese demonstrated high depression and anxiety among nurses where physical activity, rest between shifts, and spending less time searching for information about COVID-19 were related to improved mental health. 21 Correspondingly, high depression, anxiety, and stress were also reported in nurses from Brazil and the authors highlighted the units in which nurses were working and less experience as important factors in developing depression, anxiety and stress.…”
Section: Introductionmentioning
confidence: 99%